Analysing Variability Management in BPM and SPL: A Knowledge Mapping - Valença, George; Alves, Carina; Alves, Vander (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2013: Anais do IX Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2013.5747, 2013)
New government regulations, business volatility and changes on stakeholders needs are examples of process change inductors. This dynamic scenario promotes a phenomenon called business process variability. This is an emergent topic in Business Process Management (BPM) that uses Software Product Line (SPL) theoretical basis to investigate the variability of process models. This paper explores the adoption of variability concepts and theories by the BPM community, with a mapping to analyse how the variability body of knowledge has been used from SPL to the BPM field. In addition, we position current research challenges within business process variability, and discuss how concepts and theories from SPL could be used to treat these questions.